2005
DOI: 10.1074/jbc.m503684200
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Tryptophan of Escherichia coli DnaA Protein Functions in Oligomerization at the E. coli Replication Origin

Abstract: In the initiation of bacterial DNA replication, DnaA protein recruits DnaB helicase to the chromosomal origin, oriC, leading to the assemble of the replication fork machinery at this site. Because a region near the N terminus of DnaA is required for self-oligomerization and the loading of DnaB helicase at oriC, we asked if these functions are separable or interdependent by substituting many conserved amino acids in this region with alanine to identify essential residues. We show that alanine substitutions of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
92
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 42 publications
7
92
0
Order By: Relevance
“…Experimentally, residues at positions Gln3, Phe4, and Phe7 (Leu5, Trp6 and Cys9 in E.coli) have been shown to be critical for oligomerization [18,19] and residues 24-86, and in particular Pro28, have been implicated in DnaB binding [19,20]. Residues Gln3, Phe4, and Phe7 line the inner face of helix I ( Figure 3) and Pro28 is in the loop connecting helix II and β-strand I.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Experimentally, residues at positions Gln3, Phe4, and Phe7 (Leu5, Trp6 and Cys9 in E.coli) have been shown to be critical for oligomerization [18,19] and residues 24-86, and in particular Pro28, have been implicated in DnaB binding [19,20]. Residues Gln3, Phe4, and Phe7 line the inner face of helix I ( Figure 3) and Pro28 is in the loop connecting helix II and β-strand I.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed above, the results from several studies suggested that the N-terminal domain dimerizes or assists in the formation of larger oligomers [10,18,19]. Before initiating NMR studies, we probed the oligomerization state of our construct using both size exclusion chromatography (SEC) and analytical ultracentrifugation (AUC).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations